Overlooked Wordplay in Aelian’s Varia Historia 9.31 - Hollenback, George M. (Euphrosyne, 2024)
Abstract This note deals with overlooked wordplay between ἀθλητής and πτῶμα in Aelian’s Varia Historia 9.31. Although the respective words have general meanings of “athlete” and “fall”, they may also have the particular meanings of “wrestler” and “defeat or loss suffered by a wrestler”, these particular meanings perhaps being the overlooked theme of the passage.
Keywords: Ancient Olympic Games